Patterns of Femininity in the Heroic Epic. Homer: The Iliad and the Odyssey - Bodiştean, Florica (Mediterranean Journal of Social Sciences, 2012)
The aim of this study is to point out that Homer’s epics create a feminine typology that is approached indifferent life situations, in times of peace or war, a typology that will begin, in pure or hybrid forms, a realtradition in the heroic literature: the Demeter-type woman, the Aphrodite-type woman and the Amazontypewoman. If in The Odyssey women act as epic agents and are present in large numbers, in Homer’s firstepic they are backstage characters, but still relevant at the fictional level, because they play a great varietyof roles. The Odyssey reveals femininity from the point of view of man, who compares and assimilates ordifferentiates various types of women. The Iliad offers a heroic perspective on femininity: a woman whostirs the warrior attitude, a woman who accompanies the hero, a woman who engages herself in acompetition against the hero.